Desarrollo de la integración social en niños ticuna de la Institución Educativa Inicial N° 386 Bilingüe Intercultural Bellavista Callarú, Yavarí 2022 - Cayetano Almeida, Gretel (2023)
The research question was: How is the development of social integration in Ticuna children from the initial educational institution No. 386 Bilingual Intercultural located in Bellavista Callarú Yavarí? and the objective was to describe the development of social integration in Ticuna children of the educational institution. For this purpose, the type of relational research was considered with a nonexperimental, univariate, field and cross-sectional design. All Ticuna children enrolled in the institution were the population and sample. An observation guide has been the instrument to collect the data, which was validated by experts. The technique used has been observation. Conclusion: The overall results in the development of social integration show that Ticuna children present good development in 62.5% of them, 37.5% of children show regular development of social integration, while there was no Ticuna child who had deficient development of social integration.